Hydro-climatic variability comparison of results from some global circulation models applied for western Africa - Casenave, Laurence (My University, 2004)
The sharp increase in temperature observed during the past fifty years is making people more and more worried about the possible climate evolution in the future. The International Panel on Climate Change was created to find out the causes of such changes and their possible impacts. It established 40 different “Scenarios” and used a set of models in order to simulate the climate system and give an overview of the climate up to 2100. The comparison of these models in Western Africa leads to many conclusions about their reliability. A common weakness of all these models is the inability to simulate low precipitations like in the Sahelian part. On a quantitative point of view, three of them overestimate the precipitation whereas the CSIRO-Mk2 underestimates it. On a qualitative aspect, the ECHAM4/OPYC3 and HadCM3 are good in the southern part of the window (tropical humid area), whereas the PCM and the CSIRO-Mk2 are better in the northern part (Sudanese - Sahelian part). ECHAM4/OPYC3 is the only one to reproduce the two rainy seasons (Ivory Coast). The scenario comparison does not give distinct results, as the period of study is too short to distinguish differences between scenarios. (WHY IS THE PERIOD TOO SHORT? TO ME IT SEEMS THE MODELS ARE ALL INCAPABLE) Neither gives the study of future values clear results (aswers?) . No tendency can be clearly seen for the evolution of precipitations in the next hundred years. CSIRO predicts a decrease in precipitations for almost the whole western Africa, ECHAM forecasts an increase, whereas the HadCM3 and the NCAR-PCM cut the window into two parts which are different from one scenario to another. This shows that these models still have to be improved to give a better picture of the future situation.
Keywords: Samhällsbyggnadsteknik; Civil Engineering